Guiding carbon farming using interdisciplinary mixed methods mapping. Issue 2 (30th April 2019) - Brockett, Beth F. T.; Browne, Alison L.; Beanland, Andy; Whitfield, Mike G.; Watson, Nigel; Blackburn, George Alan; Bardgett, Richard D.
Abstract: In recognition of the need to address complex environmental problems, some ecological studies have adopted social research methods to better understand the complexity of social‐ecological systems management. The overwhelming majority of these studies stop short of fully embracing qualitative methodologies. The lack of integrative social and natural science data for a topic such as soil carbon farming is problematic as theoretical carbon sequestration opportunities identified through soil mapping and process‐based models can fail to deliver the sequestration levels promised when introduced on‐the‐ground. Such mapping needs to account for the human factors involved in delivering increased soil carbon on‐farm. Here, we develop a mixed methods mapping approach to explore the potential for increasing soil carbon stocks on upland farms in the UK. Our approach considers ecological and social complexity through application of soil science, ecology, participant observation, interviews and a focus group. Our maps revealed landscapes that are full of carbon farming opportunity, but contain previously hidden barriers to the delivery of increased soil carbon. For example, they revealed that carbon farming can be considered by farmers to work in opposition to perceived 'good farming' practices and be correlated with increased incidents of livestock disease. We also discovered that the use of maps in research can be problematic as they can close down discussion and exclude local representation of an area. Trialling an interdisciplinary mixed methods approach produced new, deeper and more richly‐textured understandings about how soil carbon management is produced socially as well as ecologically on upland livestock farms. Our findings have potential to improve the success of future carbon farming initiatives by incorporating farmer knowledge and social drivers of implementation. A plain language summary is available for this article. Abstract : Plain Language Summary